Activation of Peroxisome Proliferator-activated Receptor γ Prevents Development of Heart Failure With Preserved Ejection Fraction; Inhibition of Wnt-β-catenin Signaling as a Possible Mechanism. Issue 2 (August 2016) - Kamimura, Daisuke; Uchino, Kazuaki; Ishigami, Tomoaki; Hall, Michael E.; Umemura, Satoshi
Abstract : Abstract: Left ventricular (LV) fibrosis plays an important role in the development of heart failure with preserved ejection fraction (HFpEF). We investigated whether chronic peroxisome proliferator-activated receptor gamma agonism with pioglitazone can prevent the development of HFpEF. We also evaluated the role of Wnt-β-catenin signaling in the development of HFpEF, and its relationship to peroxisome proliferator-activated receptor gamma signaling. Dahl salt-sensitive rats placed on an 8% NaCl diet from age 6 weeks were used as HFpEF model. Rats placed on 0.3% NaCl diet served as controls (n = 7). HFpEF model rats were randomized to no treatment (n = 7) or treatment with pioglitazone (2.5 mg/kg per day, n = 7) at age 13 weeks. Pioglitazone administration from age 13 to 21 weeks attenuated the development of LV fibrosis and stiffening (both P < 0.05), and subsequently prevented the development of HFpEF. In the untreated HFpEF model, Wnt1, 2, 10b messenger RNA and β-catenin protein expression levels in the left ventricle increased in the heart failure stage, along with the increase in type I collagen messenger RNA expression levels. Administration of pioglitazone attenuated the activation of Wnt-β-catenin signaling. Our results show that pioglitazone prevented the development of LV fibrosis and HFpEF in a rat model, at least partly due to attenuated Wnt-β-catenin signaling.